2016
DOI: 10.1016/j.clinbiomech.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Hallux valgus surgery affects kinematic parameters during gait

Abstract: Background The aim of our study was to compare spatiotemporal parameters and lower limb and pelvis kinematics during the walking in patients with hallux valgus before and after surgery and in relation to a control group. Methods Seventeen females with hallux valgus, who underwent first metatarsal osteotomy, constituted our experimental group. The control group consisted of thirteen females. Kinematic data during walking were obtained using the Vicon MX system. Findings Our results showed that hallux valgus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 48 publications
3
33
0
1
Order By: Relevance
“…On the basis of pedobarographic examination, it was shown that in patients suffering from the degenerative disease of the hips, the plantar surface loading distribution was not even and the body weight was evidently shifted onto the healthy limb [ 21 ]. As is the case in RA, the most common types of foot deformities in OA are those of the longitudinal and transverse arches, as well as of the first metatarsophalangeal joint [ 22 , 23 ]. Recent research confirms the relation between the degree of pain intensity and the development of degenerative changes in the knee and feet joints and a fallen longitudinal arch [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of pedobarographic examination, it was shown that in patients suffering from the degenerative disease of the hips, the plantar surface loading distribution was not even and the body weight was evidently shifted onto the healthy limb [ 21 ]. As is the case in RA, the most common types of foot deformities in OA are those of the longitudinal and transverse arches, as well as of the first metatarsophalangeal joint [ 22 , 23 ]. Recent research confirms the relation between the degree of pain intensity and the development of degenerative changes in the knee and feet joints and a fallen longitudinal arch [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no significant differences in the other GRF variables between the orthosis conditions (p > 0.05) ( Table 2). subjects [15]. The repulsive force applied to the feet and toes from the ground during walking is known as a very important variable when evaluating the function of the foot and ankle joints in gait patterns and daily activities such as balance [16,17].…”
Section: Resultsmentioning
confidence: 99%
“…En la revisión se encuentran tres estudios, cinemáticos (2,24) y baropodométrico (5), que referencian la situación real del pie durante la marcha tras un procedimiento quirúrgico de HAV, pero sí mejora el patrón hiperqueratósico producido por la deformidad (5,24).…”
Section: Cirugía Tradicionalunclassified